Incidence and spread of knockdown resistance (kdr) in German Colorado potato beetle (Leptinotarsa decemlineata Say) populations. (April 2016) - Tebbe, C.; Breckheimer, B.; Racca, P.; Schorn, C.; Kleinhenz, B.; Nauen, R.
Abstract : The Colorado beetle, Leptinotarsa decemlineata (Say), is one of the most important pests in many potato‐producing regions. Colorado beetle infestations are normally kept under economic damage thresholds by applying insecticides such as pyrethroids. Pyrethroids are known to act on voltage‐gated sodium channels and have been used for several decades to control L. decemlineata . Their continuous and widespread use has resulted in the development of resistance, which is often linked to a L1014F target‐site mutation in the voltage‐gated sodium channel, known as knockdown resistance ( kdr ). Since pyrethroids are used in many potato‐growing regions in Germany, more than 140 L. decemlineata samples were collected and analysed for the presence of the kdr allele by pyrosequencing diagnostics. Results showed that kdr is present in many German L. decemlineata populations, but even its homozygous presence does not substantially compromise the efficacy of recommended label rates of pyrethroids, as demonstrated by bioassays and crossing experiments. The implications of these findings for resistance management are briefly discussed.